ON THE CONSISTENCY AND CONVERGENCE ANALYSIS OF A DERIVED EXPLICIT FOURTH-STAGE FOURTH-ORDER RUNGE-KUTTA METHOD - Christopher, Esekhaigbe Aigbedion; Aitusi, Daniel (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2022)
This paper is aimed at analyzing the consistency and convergence of a derived explicit fourth-stage fourth-order Runge-Kutta method. The analysis revealed that the method is consistent and convergent. The implementation of this method on initial-value problems was done in previous paper, and it revealed that the method compared favorably well with the existing classical fourth stage fourth order explicit Runge Kutta method